The Influence of Air Pollution and Clean Energy on Tuberculosis: The Moderating Role of Urbanization - Farzan YAHYA; Muhammad RAFIQ (Tehran University of Medical Sciences, 2020)
Background: Air pollution is one of the major threats to human health and well-being. This study aimed to explore the effect of renewable energy consumption and carbon dioxide emissions on tuberculosis (TB) incidences. It further investigates the moderating role of urbanization on the relationship between underlying factors and TB. Methods: The data of 183 countries over the period 2000 to 2014 were collected and a two-step system GMM technique was utilized to reduce the endogeneity issue. Additionally, we divided the sample into two sub-panels based on country risk for more robust estimates. Results: Carbon dioxide emissions increase the incidences of TB while renewable energy consumption could restrict these cases. On the other hand, urbanization is positively associated with TB in high-risk. System-GMM estimates also indicated that urbanization further strengthens the positive association between CO2 emissions and tuberculosis. Conclusion: Climate-friendly energy technologies, surveillance, and adequate city planning can act as effective mechanisms to improve public health.